2022
DOI: 10.24843/soca.2022.v16.i01.p06
|View full text |Cite
|
Sign up to set email alerts
|

The Household Consumption Decision of Staple Food Purchase in the Midst the Covid-19 Pandemic

Abstract: Covid-19 has brought surprising changes in the household behavior pattern and decision-making process in consuming food. Therefore, this study aimed to (1) identify household consumption pattern and purchase behavior due to the dynamics of supply shock during the Covid-19 pandemic and (2) analyze factors that influence household consumption decisions on food purchase during the Covid-19 pandemic. One hundred participants from Kaliwates and Sumbersari District, Jember Regency, had recruited by the cluster sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…On the other hand, Figure 1 shows that 53.69% of respondents bought "less" and "much less" food than usual during the COVID-19 pandemic. It is in line with Zainuddin et al (2022), which stated that people's daily income did not support food hoarding during the COVID-19 pandemic. In addition, this study also found that the COVID-19 pandemic also triggered several changes in food-related activities.…”
Section: Figure 1 Change In Shopping Patterns During Covid-19 and Psbbsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, Figure 1 shows that 53.69% of respondents bought "less" and "much less" food than usual during the COVID-19 pandemic. It is in line with Zainuddin et al (2022), which stated that people's daily income did not support food hoarding during the COVID-19 pandemic. In addition, this study also found that the COVID-19 pandemic also triggered several changes in food-related activities.…”
Section: Figure 1 Change In Shopping Patterns During Covid-19 and Psbbsupporting
confidence: 81%
“…Before the pandemic, people were not worried about traveling to buy food and groceries. At that time, they usually obtained food from markets, shops, and supermarkets (Zainuddin et al, 2022). However, such worries and concerns arose during the COVID-19 pandemic (Ben Hassen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Structured relationships can be studied with SEM using a set of equations that define the causality between constructs in an analysis. Most previous studies used regression [8,9], mixed method [10], and logit analysis [11,12] to establish a relationship between these sorts of variables. PLS-SEM (Partial Least Squares-Structural Equation Modelling) was implemented in the related study to predict food consumption behaviour models and vance associations between all constructs.…”
Section: Introductionmentioning
confidence: 99%